Law Without Justice : Why Criminal Law Doesn't Give People What They Deserve. - Robinson, Paul H. (Oxford University Press, 2005)
Offering a look at American criminal law, this book demonstrates that cases with unjust outcomes are not always irregular or unpredictable. It aims to show that the criminal law sometimes chooses not to give defendants what they deserve: that is, unsatisfying results occur even when the system works as it is designed to work.